2022
DOI: 10.1161/strokeaha.121.038155
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival, Stroke Recurrence, and Life Expectancy After an Acute Stroke in Australia and New Zealand From 2008–2017: A Population-Wide Cohort Study

Abstract: BACKGROUND: Data on long-term outcomes following an acute stroke are sparse. We assessed survival, risk of recurrent stroke and loss in life expectancy following an acute stroke using population-wide data from Australia and New Zealand. METHODS: We included all adults with the first stroke hospitalization during 2008 and 2017 at all public and most private hospitals. Patients were followed up to 10 years after the stroke by linkage to each region’s Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…In our study, the highest incidence rate of recurrence was observed for ICH in both pregnancy-associated and non–pregnancy-associated stroke, which is consistent with the literature highlighting higher stroke recurrence after ICH than other strokes . Of note, the recurrent cerebrovascular event after a first ICH was most often another ICH, thus indicating a common underlying cause of both episodes.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the highest incidence rate of recurrence was observed for ICH in both pregnancy-associated and non–pregnancy-associated stroke, which is consistent with the literature highlighting higher stroke recurrence after ICH than other strokes . Of note, the recurrent cerebrovascular event after a first ICH was most often another ICH, thus indicating a common underlying cause of both episodes.…”
Section: Discussionsupporting
confidence: 91%
“…Such differences were even more evident in both loss-of-LE and the loss-of-QALE between men and women with hemorrhagic stroke, as reported by a study from Australia and New Zealand. 30 Especially, the loss-of-QALE was bigger in men with statistical significance (p = 0.049). The major reason for the above discrepancy may arise from the different distributions of age and calendar year of diagnosis in the comparison of long-term follow-up data.…”
Section: Discussionmentioning
confidence: 92%
“…In a large national cohort of stroke patients from Australia and New Zealand, about half of patients hospitalized with a stroke survived at 5 years, and only a third at 10 years. Around one-fifth of patients had a stroke recurrence by 5 years, and 25% by 10 years ( Peng et al, 2022 ). Compared with our study from Chinese population, an acute stroke reduced the life expectancy long-term functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the data from real-world studies with large sample have shown that patients treated with endovascular therapy had longer survival times, attributable a lower risk of death within 0–90 days and extended follow-up to 2 years ( Beyeler et al, 2022 ). Despite these promising finding, much of our understanding about stroke outcomes comes from studies with relatively short follow-up time and the long-term prognosis after a stroke are sparse ( Rutten-Jacobs et al, 2013 ; Ekker et al, 2019 ; Peng et al, 2022 ). Acute stroke trials have largely assessed short-term (90 days) primary outcomes following treatment ( Yarbrough et al, 2015 ; Campbell et al, 2016 ; Goyal et al, 2016 ) and information on long-term outcomes may be useful for clinical practice and health care policy decision-making, particularly in developing countries which have a higher stroke burden, but more limited health care resources.…”
Section: Introductionmentioning
confidence: 99%